2015
DOI: 10.1111/jre.12308
|View full text |Cite
|
Sign up to set email alerts
|

α‐tocopherol decreases interleukin‐1β and ‐6 and increases human β‐defensin‐1 and ‐2 secretion in human gingival fibroblasts stimulated with Porphyromonas gingivalis lipopolysaccharide

Abstract: These results suggest that α-tocopherol may play an active role in countering the damaging effect of LPS by reducing inflammatory cytokines, increasing β-defensins and promoting fibroblast growth, migration and wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 55 publications
(60 reference statements)
0
16
0
1
Order By: Relevance
“…These results demonstrate the importance of modulation of inflammatory reactions on oral mucosa to accelerate closure of wounds. Regarding this modulation, some treatment strategies have been proposed, targeting modulation of inflammatory process 19 . Derradjia et al 19 demonstrated that application of α‐tocopherol to cells previously exposed to LPS stimulated cell viability and migration.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate the importance of modulation of inflammatory reactions on oral mucosa to accelerate closure of wounds. Regarding this modulation, some treatment strategies have been proposed, targeting modulation of inflammatory process 19 . Derradjia et al 19 demonstrated that application of α‐tocopherol to cells previously exposed to LPS stimulated cell viability and migration.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, vitamin E may have anti-inflammatory effects against P. gingivalis. 164 Antibodies or antagonists There are also some antibodies or antagonists that indirectly influence IL-1β. Infliximab is a monoclonal antibody against TNF-α.…”
Section: Other Potential Agents That Influence Il-1β In Periodontitismentioning
confidence: 99%
“…In einer In-vitro-Studie konnte gezeigt werden, dass die Applikation von Vitamin E (α-Tocopherol) die Bildung entzündungsfördernder Zytokine in humanen gingivalen Fibroblasten reduziert, wenn diese mit Lipopolysacchariden von Porphyromonas gingivalis konfrontiert werden [30]. In einer klinischen Studie korrelierte eine höhere…”
Section: Vitamin Eunclassified